UMP, Top Glove expand strategic collaboration in career development - Raja Allen Jordan Izzudin Shah, Raja Baharudin (2020)
Kuantan, 9 November 2020 - Universiti Malaysia Pahang (UMP) has forged a strategic collaboration with the largest medical glove manufacturer Top Glove Sdn. Bhd. in four areas involving students’ career development, job offers to UMP graduates, industrial training, and sponsorship that will benefit both parties.